Elementary School Teachers' Perceptions of Classroom Nutrition Education and Cafeteria Food - Lund, Kaarin (My University, 2011)
Project Overview This study was undertaken due to an interest in volunteering with Fort Riley Public Health. Being an army spouse, I was curious how Army Public Health supports our unique and constantly changing community. LTC Paul Benne, chief of Fort Riley Public Health, expressed an interest for an MPH graduate student to address obesity of active duty military personnel and their beneficiaries from the standpoint of improving nutrition on post. This objective was initially given to LTC Benne from the Irwin Army Community Hospital commander COL Michael Heimall who would allocate any necessary funding for initiatives or staff. The following objectives evolved as the study progressed. Objectives: 1. Conduct a literature review to determine an age demographic of the US population where obesity prevention/ intervention efforts should start. 2. Conduct descriptive epidemiology on Fort Riley, US Army post, to determine what nutrition initiatives are already in place and which areas have opportunities for improvement. 3. Develop, conduct and statistically analyze a survey on nutrition education and school cafeteria behaviors and use the results to make recommendations to invested partners. 4. Start the intervention. Background Initial literature reviews focused on 1) Whether childhood or adulthood was the most effective time to start nutrition interventions and 2) At what age obesity/overweight first becomes a problem in those at risk. I visited a variety of on-post establishments that serve/sell food that may or may not contribute to obesity. These visits included military dining facilities, commercial dining facilities (Burger King, Dominoes, etc), child development centers (infants-5 year olds), school cafeterias, and the commissary (grocery store). Upon visiting these sites and conducting the literature reviews, I designed 3 courses of action to address obesity/nutrition focusing specifically on elementary schools, military dining facilities, and commercial dining facilities. These were presented to COL Heimall and the deputy commander for health services at the hospital, COL Reynold Mosier. They determined that all recommendations had value and that each should be pursued. Additionally, they wanted to expand elementary school nutrition initiatives to all of USD 383 and 475 school districts instead of schools specifically on post. LTC Benne and I therefore decided to start with the elementary schools because the literature reviews identified childhood as a time to focus interventions for proper nutrition and obesity prevention. Other courses of action will be pursued by future MPH interns as phases of a nutrition promotion initiative on post.
Keywords: Classroom nutrition; Cafeteria food; Fort Riley; Nutrition interventions; Teachers' perception; Public Health (0573)